Material truth in polish criminal procedure in the perspective of planed amendments in the criminal procedure code - Przygucki, Paweł (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
The aim of the article is to present how the material truth principle will change according to an amendment to the Polish Criminal Procedure Code, which will come into force on 1st January 2015. The amendment reduces an inquisitorial role that court plays under current regulations by transfering a duty of introducing evidence to litigators. In this article there is an attempt to present possible dangers connected with such regulations. Specifically, the major stress was put onto answering the question how the public prosecution would tackle that issue and how it would influence the material truth principle. The author attempted to show that a dispute about making criminal procedure more contradictorial is in fact a conflict between basic principles of criminal trial, which is the material truth priciple. and effectiveness directive.